A blue phase liquid crystal Fresnel lens with large transverse electric field component. Issue 5 (9th April 2021) - Dou, Hu; Wang, Lu; Chu, Fan; Zhang, Sheng-Dong; Wang, Qiong-Hua
ABSTRACT: A Fresnel lens with blue phase liquid crystal (BPLC) material is proposed, and the mainly electrical field in BPLC layer is parallel to substrates. The structure and proportion of the applied voltage on every Fresnel zones is constant, through adjusting the voltage applied on the edges of Fresnel zones, the focal length can be tuned. Moreover, by increasing the number of the identical Fresnel zones of the BPLC lens, a BPLC lens with a larger aperture can be easily obtained, and the light control power is also high while maintaining a fast response time and a thin BPLC layer. Graphical abstract: